2018
DOI: 10.1002/jib.481
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition of hop secondary metabolites induced by high hydrostatic pressure

Abstract: Hops contain large amounts of secondary metabolites, many of which have notable bioactive and sensory characteristics. Many of these properties are affected by the processing of raw hops into products. We studied the influence of high‐pressure processing (HPP) on the content and composition of secondary metabolites in hop homogenates prepared from fresh green cones of several Czech hop varieties. Homogenates contained more hop oils (27% on average) compared to dried hops. The composition of essential oils in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…HHP extraction, compared with all other techniques, allowed to extract a limited number of VOCs (18 out of 34 compounds). Since other authors (Krofta et al, 2018) investigating the volatile profile of fresh hops homogenates subjected to high hydrostatic pressure processes did not find any loss of VOCs, this result highlights the lower capability of HHP at the conditions applied in this study to extract these volatile secondary metabolites.…”
Section: Relative Cohumulonesupporting
confidence: 46%
See 2 more Smart Citations
“…HHP extraction, compared with all other techniques, allowed to extract a limited number of VOCs (18 out of 34 compounds). Since other authors (Krofta et al, 2018) investigating the volatile profile of fresh hops homogenates subjected to high hydrostatic pressure processes did not find any loss of VOCs, this result highlights the lower capability of HHP at the conditions applied in this study to extract these volatile secondary metabolites.…”
Section: Relative Cohumulonesupporting
confidence: 46%
“…Hop cones, the female inflorescences of Humulus lupulus L., are known worldwide as the main ingredient in the production of beer, which confer the essential character of bitterness and the overall flavor including the typical “spicy” or “hoppy” aroma (De Keukeleire et al., 2003; Krofta et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed an inhibitory potential of all PBPs in a concentration-dependent manner (Figure 3). R H -PBP was obtained from female hop cones which accumulate a great amount of secondary metabolites such as xanthohumol and other derivatives, with strong antimicrobial activity against anaerobic or ruminal bacteria [49,50]. In this line, equisetum (E-PBP in this study) has shown antibiotic activity against some Gram-positive bacteria and oomycetes [51,52].…”
Section: Discussionmentioning
confidence: 97%
“…It is possible to prepare a homogeneous mass by mixing the fresh plants, treat this mass with high pressure and then use it as a semi-finished product in various dishes [ 54 , 55 ]. The herbs homogenate preparations represent a proven method of fresh herbs processing without heating or freezing and a method when biologically active substances are preserved [ 56 ].…”
Section: Sodium Occurrence In Foods and Possibilities Of Its Reductionmentioning
confidence: 99%